Rancang Bangun Sistem Transmisi Pada E-Bike of PPNS - Muh. Halim Nur Aziz; Tri Andi Setiawan; Fipka Bisono (Proceedings Conference On Design Manufacture Engineering And Its Application, 2023)
Transportation is a basic need and plays an important role to support people's daily activities. However, over time, traffic density cannot be handled properly so that it causes traffic irregularities, air pollution, and wasteful use of fuel energy. The need for fuel oil has increased drastically, causing an increase in the price of fuel oil which until now the price is still unstable. Since the decline in vehicle mobility caused by the lockdown, the level of air pollution has decreased compared to before the COVID-19 pandemic. The existence of alternatives and new breakthroughs in vehicles that are more environmentally friendly and efficient based on electricity is an option due to the use of renewable energy such as electric bicycles. The vehicle is currently undergoing very rapid development so that with this innovation it can support the vision of the Indonesian state to achieve Net Zero Emissions in 2060. To achieve this, it can be done by developing a transmission system on bicycles to increase optimal power efficiency and save power so that in the future these bicycles can be used for longer distances. To solve this problem the author uses the Ulrich method. Of the three designs made, a design with a flywheel and motor drive was chosen which was combined into 2 shafts, one of which later became the pedal shaft for the bicycle pedal. Then, the cost of making this transmission system itself costs IDR 3,315,000.